THE RELATIONSHIP BETWEEN MEDIA CONSUMPTION AND FEAR OF CRIME: A COMPREHENSIVE REVIEW - De Silva, Banuka (JURNAL ILMU BUDAYA, 2023)
This comprehensive review examines media consumption and crime fear. Due to the media's focus on sensational crimes and its influence on people's perceptions of reality, most studies show a positive correlation between media consumption and fear of crime. Several studies have found a negative correlation between media consumer awareness and desensitisation. Responsible reporting and media literacy programmes reduce crime fear. Media literacy helps people understand crime and recognise media sensationalism. To promote a less distorted view of crime, media outlets must report crime news accurately and objectively without exaggerating events. Despite its limitations, this review's systematic approach and search strategy provide a comprehensive and trustworthy overview of media consumption and fear of crime research. The relationship's mechanisms and contextual factors need further study. This analysis indicates how media consumption affects public perceptions of crime and safety.